La loi paysage a-t-elle eu un impact sur la planification territoriale ? - Didier Labat; Gaelle Aggeri (Projets de Paysage)
We question the impact of the Landscape Law, concerning procedures of spatial planning and the evolution of competencies among public project owners. The examples developed indeed illustrate how a new landscape planning is emerging at the initiative of collectivities, while conforming as closely as possible to citizen requests and participation and relying upon a new mobilization within the framework of the changing competencies of divers landscape actors, experts and people in the know. Our analysis shows that in parallel with better use of the landscape in planning tools there is also growing evidence of a conflict of representation between the requirements rooted in the Grenelle of the environment and the reinforcement of cross-cutting competencies in the field of project management among the trades involving project promoters. In the end, inclusion of the landscape is not simply a matter of legislative measures. Ultimately changes in public action imply above all that the professionals involved adapt themselves to societal expectations concerning the living environment and habits.